1981
DOI: 10.1139/m81-137
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis distribution in soils of the United States

Abstract: During a 2-year study, samples of various types of soils were collected from 115 fields that had not previously been tested with Bacillus thuringiensis and which were remote from any large-scale aggregations of lepidopterous insects in rearing or grain-storage areas. An average of about 400 isolates were examined from each soil, and, of 46 373 isolates examined, only 250 (0.5%) were identified as B. thuringiensis. While it was almost impossible to insure that a field had never been treated with B. thuringiensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 9 publications
(9 reference statements)
3
43
1
3
Order By: Relevance
“…In the spring, a number of isolates (70%) were toxic to lepidopteran larvae, which was consistent with previous reports (DeLucca et al, 1981(DeLucca et al, , 1982Karamanlidou et al, 1991;Martin and Travers, 1989;Ohba and Aizawa, 1986a;Ohba et al, 1984;Smith and Couche, 1991). Lepidopteran/ dipteran-active isolates were 19% in the spring and 62% in the fall.…”
Section: Parasporal Inclusion Morphology and Qualitative Insecticidalsupporting
confidence: 90%
See 1 more Smart Citation
“…In the spring, a number of isolates (70%) were toxic to lepidopteran larvae, which was consistent with previous reports (DeLucca et al, 1981(DeLucca et al, , 1982Karamanlidou et al, 1991;Martin and Travers, 1989;Ohba and Aizawa, 1986a;Ohba et al, 1984;Smith and Couche, 1991). Lepidopteran/ dipteran-active isolates were 19% in the spring and 62% in the fall.…”
Section: Parasporal Inclusion Morphology and Qualitative Insecticidalsupporting
confidence: 90%
“…Since B. thuringiensis was first discovered in an insect cadaver, a large number of B. thuringiensis strains have been isolated (Berliner, 1915;Ishiwata, 1901). Since that time, researchers have been interested in isolating B. thuringiensis in insect-favoring habitats and have also reported the isolation of B. thuringiensis from soils (DeLucca et al, 1981), sericultural farms (Ohba et al, 1984), stored grains (DeLucca et al, 1982), phylloplanes of plants (Smith and Couche, 1991), ponds (Goldberg and Margalit, 1977), etc.…”
mentioning
confidence: 99%
“…The incidence of Bt in Yemen soils seems to be more frequent than in soils of United States [18] and Saudi Arabia [10], where 17 and 8 % of their isolates were producing parasporal inclusions respectively. A total of 65 % of parasporal inclusions of identified Bt were bipyramidal in shape followed by 26 % of spherical shape crystals and 0.1 % only of various shaped of crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Although B.t. is common in soil microbiota (DeLucca et al 1981;Martin and Travers 1989), it has never been observed to control forest insect pest populations in nature and must be applied as an insecticidal spray.…”
Section: Microbial Agentsmentioning
confidence: 99%